2020
DOI: 10.31590/ejosat.734204
|View full text |Cite
|
Sign up to set email alerts
|

Piyasada Satılan Ticari Propolis Örneklerinin Biyoaktif Bileşenlerinin Belirlenmesi

Abstract: Öz Tüketicilerin gıda ve içerikleri hakkında daha bilinçli hale gelmesi, sağlık faydası olan fonksiyonel gıdaları tercih etmeleri nedeniyle gıda ürünlerinin biyoaktif bileşenlerinin incelenmesi önemli hale gelmiştir. Yapılan bilimsel çalışmalarla içerdiği biyoaktif maddeler nedeniyle birçok sağlık faydası tespit edilen propolis, tüketiciler tarafından takviye edici gıda olarak tercih edilen ürünler arasında ilk sıralarda yer almaktadır. Ancak ülkemizde Helal gıda kapsamında alkol kullanılmadan farklı çözgen ek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, the presence of alcohol in the extract limits its application in cosmetic, pharmaceutical, nutraceutical, and pediatric products and leads to the exploration of non‐alcoholic extraction solvents. There are different PEs sold on the market as food supplements produced by alternative natural (e.g., water and olive oil) and alcohol derivative extraction solvents (e.g., propylene glycol and glycerin) (Sagdic et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of alcohol in the extract limits its application in cosmetic, pharmaceutical, nutraceutical, and pediatric products and leads to the exploration of non‐alcoholic extraction solvents. There are different PEs sold on the market as food supplements produced by alternative natural (e.g., water and olive oil) and alcohol derivative extraction solvents (e.g., propylene glycol and glycerin) (Sagdic et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of natural extraction solvents may not be proper for the desired phenolic composition in the PE (Kubiliene et al., 2018 ; Sagdic et al., 2020 ). Even though glycerin does not have an ADI value, it has been observed that its potential to dissolve propolis is considerably less than ethanol The adverse effects of propylene glycol consumption have been reported previously (Atayoglu et al., 2023 ; Bakkaloglu & Arici, 2019 ; Sagdic et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%